2007
DOI: 10.1111/j.1600-0404.2006.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of midbrain atrophy in patients with progressive supranuclear palsy with routine magnetic resonance imaging

Abstract: Morphological indexes indicate midbrain atrophy in PSP patients The combination of the A(ms) and A(ms)/A(pn) ratio measurements allows to discriminate between PSP and other conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 26 publications
2
88
0
Order By: Relevance
“…using Analyze software (Biomedical Imaging Resource; Mayo Clinic, Rochester, MN), based on previously published criteria. 4,18 PiB-PET scans were classified as positive or negative according to previously published criteria. 4 Global PiB ratios were calculated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…using Analyze software (Biomedical Imaging Resource; Mayo Clinic, Rochester, MN), based on previously published criteria. 4,18 PiB-PET scans were classified as positive or negative according to previously published criteria. 4 Global PiB ratios were calculated.…”
mentioning
confidence: 99%
“…Measurements of midbrain area were performed on volumetric MRI because midbrain atrophy is a feature of PSPS, [18][19][20] a tauopathy associated with AOS. 21,22 Measurements were performed manually by one rater (J.L.W.)…”
mentioning
confidence: 99%
“…Previously, conventional magnetic resonance imaging (MRI) revealed important characteristic findings that can be used in clinical practice to differentiate among parkinsonian syndromes 5 . Objective quantifications of midbrain and pons using linear, surface and volumetric measurements have been reported before [6][7][8][9][10] . In these studies, two-point comparisons were made correlating each parkinsonian syndrome and PD.…”
mentioning
confidence: 99%
“…However, clinical differentiation of PSP from PD and multiplesystem atrophy of Parkinson can be difficult, particularly in early stages of the disease. MRI studies on PSP have shown atrophy of the midbrain and pons in mid-sagittal sections, hence aiding in its diagnosis [6]. The goal of this case report is to highlight the usefulness of MRI brain in diagnosing PSP, especially in its early stages, and preventing its misdiagnosis as PD.…”
Section: Introductionmentioning
confidence: 99%